Mannose-binding lectin gene (MBL-2) polymorphism in oral lichen planus. - Barkokebas, Andreza; de Albuquerque T Carvalho, Alessandra; de Souza, Paulo Roberto Eleutério; Gomez, Ricardo Santiago; Xavier, Guilherme Machado; Ribeiro, Camila Maria Beder; Crovella, Sergio; Porter, Stephen Ross; Leão, Jair Carneiro (Clin Oral Investig, 2011)
TNF-α may be associated with the etiopathogenesis of oral lichen planus (OLP), and it has been suggested that polymorphism of mannose-binding lectin (MBL) increases the in vitro production of TNF- α. The aim of the present study was to assess the relevance of genetic diversity of MBL in OLP. The study sample comprised 90 individuals, 45 OLP patients and 45 healthy volunteers. MBL-2 gene was amplified using real-time PCR. Frequency of A/A genotype was 55.6% in OLP and 53.3% in healthy volunteers. Likewise, A/0 heterozygote genotype was found in 42.2% and 35.6%; 2.2% and 11.1%, had the recessive 0/0 genotype respectively. Frequencies of the "A" and "0" alleles were 77% and 23% in the OLP group and 71.2% in control group. There were no statistically significant differences regarding genotype frequency (p = 0.546) or allele frequency (p = 0.497). In conclusion, no significant association was found between polymorphism of MBL-2 gene and OLP.
Keywords: Adolescent; Adult; Aged; Female; Gene Expression Regulation; Gene Frequency; Genes, Recessive; Genetic Variation; Genotype; Heterozygote; Homozygote; Humans; Lichen Planus, Oral; Male; Mannose-Binding Lectin; Middle Aged; Mutation; Polymorphism, Genetic; Real-Time Polymerase Chain Reaction; Tumor Necrosis Factor-alpha; Young Adult